2020
DOI: 10.3389/fmars.2020.581945
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan

Abstract: Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Whilst these initiatives are very important and may enable protecting key functional species (e.g. species that might limit algal proliferation; Bellwood et al, 2006b; Burkepile & Hay, 2011; Dang et al, 2020; Kuempel & Altieri, 2017), there is still an extremely poor understanding on the mechanisms that drive and reinforce non‐algal alternative communities (González‐Rivero et al, 2012). Therefore, a better understanding of the drivers, reinforcing mechanisms and the persistence of non‐algal alternative communities is urgently required to design appropriate conservation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these initiatives are very important and may enable protecting key functional species (e.g. species that might limit algal proliferation; Bellwood et al, 2006b; Burkepile & Hay, 2011; Dang et al, 2020; Kuempel & Altieri, 2017), there is still an extremely poor understanding on the mechanisms that drive and reinforce non‐algal alternative communities (González‐Rivero et al, 2012). Therefore, a better understanding of the drivers, reinforcing mechanisms and the persistence of non‐algal alternative communities is urgently required to design appropriate conservation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In moderate numbers, sea urchins also play a key functional role in maintaining levels of algal growth and can substitute for fish when these are reduced or absent (Bellwood et al, 2004;Graham et al, 2013). Their effective grazing has particularly been highlighted to facilitate coral recovery following disturbances, by promoting coral recruitment and reef resilience (Carpenter and Edmunds, 2006;Dang et al, 2020a;Dang et al, 2020b;Nozawa et al, 2020). Contrary to expectation, the majority of the investigated reefs, particularly those with the greatest coral mortality, showed a decline in sea urchin densities.…”
Section: Influence On Herbivoresmentioning
confidence: 99%
“…A population of sea urchin in an area could potentially reduce algae cover by 30 to 60%, facilitating the attachment of coral juveniles by opens up a living space for coral recruitments (Dang et al 2020a;Nozawa et al 2020). Although several studies reported that the dominance of sea urchins in waters has the potential to reduce the space for coral attachment through a bioeroder mechanism (Peyrot-Clausade et al 2000), the density of sea urchins in Senggigi Beach cannot yet be categorized as potentially damaging the settlement space for coral recruitment as the threatening aggregation of sea urchin supposed to be more than 16 ind•m -2 (Dang et al 2020b).…”
Section: Density Of Megabenthic Faunamentioning
confidence: 99%